2010
DOI: 10.1007/s12519-010-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in neonatal tetanus: a 15-year experience in Sagamu, Nigeria

Abstract: The mortality rate in infants with NNT remains signifi cantly high in Nigeria. Improved maternal anti-tetanus vaccination and timely recognition and treatment of affected infants may jointly reduce the incidence and fatality rate of NNT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…6 However, hospital-based data of pediatric tetanus cases from various Third World countries clearly show that the disease is still endemic in these parts of the world, with varying incidences. 1,3,4,7 This study shows relatively high average tetanus admissions in the post-neonatal age group, with nearly 42 cases per year, higher than most studies and also higher than those reported earlier from hospitals of India. 8,9 Our centre being a referral children's hospital with a special tetanus ward could possibly explain the high admission rate.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…6 However, hospital-based data of pediatric tetanus cases from various Third World countries clearly show that the disease is still endemic in these parts of the world, with varying incidences. 1,3,4,7 This study shows relatively high average tetanus admissions in the post-neonatal age group, with nearly 42 cases per year, higher than most studies and also higher than those reported earlier from hospitals of India. 8,9 Our centre being a referral children's hospital with a special tetanus ward could possibly explain the high admission rate.…”
Section: Discussionmentioning
confidence: 50%
“…1,3,7 Thus, this study identifies an important issue of focus for health policy makers, namely that prompt treatment of suppurative otitis media and reviewing the immunization status of such patients can prevent tetanus.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is not surprising as noted in this study that, caregiver's partner's education, is associated with patronage of pharmacy store and medicine vendors and to some extent home care for managing diarrhoea episode. In addition, the decision of the educated caregivers to use home treatment, have been attributed to their ability to utilize health information wisely[38]. …”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be attributed to several factors, including the severity of illness at presentation, the limited number of skilled intensive care personnel, the inadequate facilities, and the high incidence of associated sepsis [3,7,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Although some data on neonatal tetanus in western parts of Nigeria have been recently published by Ogunlesi et al [6] and Fatuga et al [7], only cases seen towards the end of the last millennium have been considered. Therefore, to assess the progress made so far in the elimination of neonatal tetanus in Nigeria, the incidence and the outcome of the disease in Zaria were examined.…”
Section: Introductionmentioning
confidence: 99%